2010
DOI: 10.1002/mrm.22253
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the venous output function from MR signal phase: Feasibility for quantitative DCE-MRI in human brain

Abstract: For dynamic contrast-enhanced MRI studies in the human brain, it is useful to measure the venous output function (VOF). The purpose of this work was to explore the feasibility of measuring the VOF using the MR signal phase (in absolute units of gadolinium concentration) in the superior sagittal sinus. Phantom experiments were performed to validate the technique for different superior sagittal sinus angles (h 5 0-488 relative to the main magnetic field), different curvatures (straight or radius 5 45 mm), and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 36 publications
3
50
0
Order By: Relevance
“…8 The authors obtained a median transfer constant for grade IV gliomas of 0.107 minutes Ϫ1 , which is similar to our K trans _SI of 0.15 minutes Ϫ1 . They also found a statistically significant difference between the transfer constants for grade III and IV gliomas but not between grades II and III, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…8 The authors obtained a median transfer constant for grade IV gliomas of 0.107 minutes Ϫ1 , which is similar to our K trans _SI of 0.15 minutes Ϫ1 . They also found a statistically significant difference between the transfer constants for grade III and IV gliomas but not between grades II and III, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 86%
“…8,9,15 For that reason, some authors have proposed performing 2 injections of 0.05 mmol/kg of gadolinium for DCE MR imaging to minimize the error arising from the conversion of signal intensity to gadolinium concentration from magnitude images. 16 While saturation of signal intensity could lead to an underestimation of the contrast agent concentration, the presence of inflow effects could lead to an overestimation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Recently, some au-thors have suggested that measuring changes in the phase of the MR signal rather than its magnitude following gadolinium injection might provide a more accurate VIF because phase change inside the vessel is linearly related to the concentration of contrast agent. [9][10][11][12] While measurement of precontrast tissue T1 is typically included in DCE-MR imaging studies, an additional measurement of tissue T1 postinjection ("bookend" method) might also improve the reproducibility of perfusion values in gliomas. 13,14 To our knowledge, there have been few comparative studies between DCE and DSC imaging in patients with gliomas.…”
mentioning
confidence: 99%